Accelerated telomere shortening in adrenal zona reticularis in patients with prolonged critical illness - Nonaka, Keisuke; Takubo, Kaiyo; Aida, Junko; Watai, Yoriko; Komatsu, Akiko; Gomi, Fujiya; Shichi, Yuuki; Yamazaki, Yuto; Ishiwata, Toshiyuki; Sasano, Hironobu; Arai, Tomio (Frontiers in Endocrinology, 2023)
Background The number of patients with prolonged critical illness (PCI) has been increasing in many countries, and the adrenal gland plays an important role in maintaining homeostasis during PCI. Chronic disease burden is reportedly associated with shorter telomere lengths in human tissues. Telomere shortening in human somatic cells is largely dependent on cell divisions, and critically short telomeres lead to cellular dysfunction and aging. However, the association between PCI and telomere lengths in human adrenal cells is poorly understood. In this study, we investigated this association to assess whether the burden of PCI could accelerate the aging process in adrenal cells. Methods Adrenocortical tissues from patients who died after PCI usually show a diffuse pattern of intracellular cholesterol ester depletion (i.e., lipid depletion). This study examined near-normal adrenal glands obtained from autopsied patients who died suddenly (control group) and lipid-depleted adrenal glands obtained from autopsied patients who died after PCI (PCI group). The control group included 7 men aged 80 to 94 years (mean age: 85.3 years) and 7 women aged 84 to 94 years (mean age: 87.7 years). The PCI group included 10 men aged 71 to 88 years (mean age: 78.8 years) and 8 women aged 77 to 95 years (mean age: 85.6 years). By using quantitative fluorescence in situ hybridization, relative telomere lengths (RTLs) were determined in the parenchymal cells of the three adrenocortical zones (zona glomerulosa, zona fasciculata, and zona reticularis [ZR]) and in the chromaffin cells of the medulla. The number of adrenal parenchymal cells was determined by immunohistochemistry and digital image analysis. Results RTLs in ZR cells were significantly shorter in the PCI group than in the control group for both men and women (P = 0.0001 for men and P = 0.0012 for women). However, RTLs in the remaining three types of adrenal cells did not differ between the control and PCI groups for both men and women. The number of ZR cells was higher in the PCI group than in the control group for both men and women (P < 0.0001 for both men and women). The proportion of the number of ZR cells to the total number of adrenocortical parenchymal cells was also higher in the PCI group than in the control group (P < 0.0001 for both men and women). The Ki-67 proliferation index in ZR cells was higher in the PCI group than in the control group (P = 0.0039 for men and P = 0.0063 for women). Conclusions This study demonstrated ZR cell-specific telomere shortening in patients with adrenal lipid depletion who died after PCI. Our results suggest that the reactive proliferation of ZR cells accelerates the telomere shortening and aging process in ZR cells in these patients. The results of our study may contribute to the understanding of adrenal aging during PCI.